JAPAN STUDIES IN KAZAKHSTAN: AN OVERVIEW OF THE ANNUAL REPORTS OF EXPERTS FROM THE JF (Journal of Oriental Studies, 2018)
The article provides a brief overview of the current condition of Japanese studies in the Republic of Kazakhstan, current issues and tasks in the study of the Japanese language in Kazakhstan. This article is dedicated to the 25th anniversary of the Divison of Japanese Studies of the Faculty of Oriental Studies of al-Farabi Kazakh National University. The review of the dynamics of quantitative and qualitative changes of the teaching staff and students, the deep analysis of the annual reports of the Japanese Foundation experts from 2002 to 2017 are reviewed in detail.